Peran Budaya Organisasi dalam Meningkatkan Kinerja Bank Mandiri Area Banda Aceh - Teuku Muana Refi; Jamali Jamali (Universitas Batanghari Jambi, 2020)
This study aims to analyze the influence of organizational culture on the performance of Bank Mandiri of Banda Aceh region, as well as the role of organizational commitment in mediating the functional relationship between the two variables. The research sample was 156 employees who were taken by purposive sampling. The questionnaires were utilized to data collection process, and then the statistical model used to analyze the relationship between variables consists of structural equation modeling. The study found that organizational culture has a positive and significant effect on organizational commitment and the bank performance. The existence of organizational commitment mediates the influence of organizational culture on the performance of independent banks. The role of mediation is a partial mediation.